Effects of medium chain fatty acids on weanling pig growth - Schneider, Channing E.; Lerner, Anne B.; Jones, Cassandra K. (My University, 2019)
Increasing consumer demand of the livestock industry requires additional research on the diets fed to animals meant for human consumption. The drugs carbadox and zinc oxide are used in weanling pig diets to prevent E. coli and stimulate growth performance. However, these drugs have recently been linked to human health and environmental hazards. Medium chain fatty acids (MCFA) may be an alternative ingredient that can be used to prevent E. coli. The objective of this study was to test MCFA as a replacement to carbadox and zinc oxide in weanling pig diets to prevent E. coli and stimulate growth performance. Testing included 360 weaned pigs (DNA 200×400, BW 5.4kg ± 0.07kg), 10 pens/treatment, and six pigs/pen. The diets tested: 1) control, 2) 3000ppm zinc oxide phase 1 and 1500ppm phase 2, 3) 50g/ton Mecadox, 4) 1% blend C6:C8:C10, 5) 1% feed energy R2 (Feed Energy Corp, Des Moines, IA), 6) 1% FORMI GML (ADDCON, Bitterfeld-Wolfen, Germany). This experiment had three phases. Treatment diets were fed through phases one and two (days 0 to 19) and common diet was fed through phase three (days 20 to 35). All pigs were weighed once a week and feeders were weighed between each phase to collect ADG, ADFI, and G:F. Data was analyzed using PROC GLIMMIX (SAS version 9.4; Cary, NC). The data showed carbadox and zinc oxide still to be the most effective feed additives in relation to ADG and ADFI (P = 0.05). However, the pigs on the FORMI feed additive showed close resemblance in growth data to those on carbadox and zinc oxide. FORMI shows promise for future investigation as a potential drug replacement in weanling pig diets.
Keywords: Spring 2019